Effect of teneligliptin vs metformin on glycemic control in Indian patients with newly-diagnosed, drug-naïve type 2 diabetes mellitus: a 12-week randomized comparative clinical study - Raghavan, Vijay; Lahiri, Apala; K., Akul S.; Goswami, Utpal; Gupta, Chandra Narayan; Sen, Sukanta (International Journal of Advances in Medicine, 2019)
Background: This comparative study was done to evaluate the change from baseline in HbA1c levels with teneligliptin vs. metformin treatments at week 12 among recently diagnosed type 2 DM patients attending Medicine OPD of Dr. B. C. Roy Hospital, Haldia, West Bengal (a tertiary care teaching hospital). Methods: In this prospective parallel group clinical study patients were divided into two groups. Group A patients were on metformin monotherapy therapy and Group B patients were on teneligliptin monotherapy. Data of 40 patients (20 patients in each group) were available for analysis in the present study. Secondary endpoints included changes from baseline FPG and 2h-PPG values at 12 weeks were evaluated. Safety and tolerability were assessed by the incidence of adverse events (AEs) throughout the study period. Results: The mean age of patients was 50.05±12.35 years and out of the entire patient population 70% were males and 30% were females. At the end of 12 weeks or 3 months of metformin therapy, mean HbA1c, FBG, and PPG were significantly reduced by 0.52%, 16.2mg/dL, and 36.8mg/dL, respectively, and 37.75% of patients achieved the HbA1c target of <7%. At the end of 12 weeks or 3 months of teneligliptin therapy, mean HbA1c, FBG, and PPG were significantly reduced by 0.60%, 19.4mg/dL, and 49.8mg/dL, respectively (Table 2), and 40% of patients achieved the HbA1c target of <7%. Conclusions: Teneligliptin, a DPP4 inhibitor reduced HbA1C significantly compared with monotherapy of metformin in treatment naive patients at week 12. It also reduced FBG and 2-h PPBG as compared with metformin at week 12.